Managing power supply interruptions: A bottom-up spatial (frontier) model with an application to a Spanish electricity network - Pablo Argüelles; Luis Orea (Copenhagen Business School (CBS), Department of Economics, 2020)
In December 2013 a new electricity law was approved in Spain as part of an electricity market reform including a new remuneration scheme for distribution companies. This remuneration scheme was updated in December 2019 and the new regulatory framework introduced a series of relevant modifications that aim to encourage the regulated firms to reduce their power supply interruptions using a benchmarking approach. While some managerial decisions can prevent electricity power supply interruptions, other managerial decisions are more oriented to mitigate the consequences of these interruptions. This paper examines the second type of decisions using a unique dataset on the power supply interruptions of a Spanish distribution company network between 2013 and 2019. We focus on the effect of grid automatization on the restoration times, the relative efficiency of the maintenance staff, and the importance of its location. We combine a bottom-up spatial model and a stochastic frontier model to examine respectively external and internal power supply interruptions at municipal level. This model resembles the conventional spatial autoregressive models but differs from them in several important aspects.
hdl:10398/9806
Keywords: 330; electricity distribution; power supply interruptions; spatial econometrics; frontier models